2020
DOI: 10.1111/jfpp.15078
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of pulsed ultrasonic‐assisted extraction of punicalagin from pomegranate ( Punica granatum ) peel: A comparison between response surface methodology and artificial neural network‐multiobjective genetic algorithm

Abstract: The present study focuses on the valorization of pomegranate peel waste by extracting bioactive compounds (mainly punicalagin) through pulsed ultrasonic‐assisted extraction. Response surface methodology (RSM) and artificial neural network coupled with multiobjective genetic algorithm (ANN‐MOGA) were used to determine the optimum extraction condition, namely, solvent volume, amplitude, time, and duty cycle. The responses for the optimization process include punicalagin content, ellagic acid, antioxidant activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Nonetheless, the main drawbacks of those extraction processes are of large amount of solvents, longer time of treatment, higher consumption of energy, and lower extraction efficiency (Tiwari, 2015). As a consequence, in order to overcome these shortcomings associated with conventional extraction methods, various new techniques, such as ultrasound‐assisted extraction (Dranca & Oroian, 2019; Xue, Tan, Li, Cai, & Tang, 2021), microwave‐assisted extraction (González de Peredo et al, 2018), supercritical carbon dioxide extraction (Paes et al, 2014), and other novel extraction approaches (Budiene et al, 2021; Rakshit & Srivastav, 2021; Tzanova et al, 2020; Xue, Tan, Li, Tang, & Cai, 2021), have been developed for the extraction of anthocyanins from various plant materials.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the main drawbacks of those extraction processes are of large amount of solvents, longer time of treatment, higher consumption of energy, and lower extraction efficiency (Tiwari, 2015). As a consequence, in order to overcome these shortcomings associated with conventional extraction methods, various new techniques, such as ultrasound‐assisted extraction (Dranca & Oroian, 2019; Xue, Tan, Li, Cai, & Tang, 2021), microwave‐assisted extraction (González de Peredo et al, 2018), supercritical carbon dioxide extraction (Paes et al, 2014), and other novel extraction approaches (Budiene et al, 2021; Rakshit & Srivastav, 2021; Tzanova et al, 2020; Xue, Tan, Li, Tang, & Cai, 2021), have been developed for the extraction of anthocyanins from various plant materials.…”
Section: Introductionmentioning
confidence: 99%
“…The ANN approach also demonstrated superiority in the optimization step with higher recovery and less variation range between optimized and validated values. Several other studies have also demonstrated improved predictive accuracy of RSM in combination approach for optimization of the extraction of bioactive compounds 48,51,61,66‐68 …”
Section: Challenges and Way Forward For Rsm In Extraction Processesmentioning
confidence: 96%
“…Several other studies have also demonstrated improved predictive accuracy of RSM in combination approach for optimization of the extraction of bioactive compounds. 48,51,61,[66][67][68]…”
Section: Challenges and Way Forward For Rsm In Extraction Processesmentioning
confidence: 99%
“…However, the larger the hidden layer's number of neurons, the longer it takes to process the data and learn the noise. 36 Therefore, a solid network is required to determine an accurate ANN architecture to obtain accurate predictions, and this step was developed through trial and error. 37 This was done to achieve the minimum possible deviation between predic- MSE is a statistic that represents the average of the squares of the errors, the magnitude by which the value indicated by the model varies from the quantity to be observed; when MSE reaches zero, it indicates that our model's error reduces.…”
Section: Prediction With Annmentioning
confidence: 99%